Palaearctic species of the Spathius exarator species group (Hymenoptera: Braconidae: Doryctinae) with entirely sculptured mesopleuron - Belokobylskij, Sergey A.; Samartsev, Konstantin G. (Zootaxa, 2014)
The Palaearctic species of the S. exarator species group of the genus Spathius Nees with entirely sculptured mesopleuron are discussed. Four new species, Spathius austriacus sp. nov., S. intercontinentalis sp. nov., S. pseudodentatus sp. nov., and S. sculptipleurum sp. nov., are described and illustrated. Spathius curvicaudis Ratzeburg, 1944 treated here as junior synonym of S. erythrocephalus Wesmael, 1838 (syn. nov.) The key for determination of the Palaearctic species of this group with constantly or temporary sculptured mesopleuron is provided.